2018
DOI: 10.3390/fermentation4010002
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Volatile Fatty Acid Build-Up by the Use of Soft Carbon Felt Electrodes: Evaluation of Anaerobic Digestion in Acidic Conditions

Abstract: Anaerobic digestion and bioelectrochemical systems have great potential to recover energy from waste streams and help overcome common hurdles associated with this process, as integrated technologies. In this study, the benefit of integrating an electrogen-enriched bioanode in a batch anaerobic digester was explored under ambient temperature conditions associated with organic overloading and reactor acidity. An increase in CH 4 production was observed in the electrode-containing reactors (0.56 L CH 4 kg VS −1 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 42 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…This increment was explained by the electron contribution from the microbial electrolysis system. Moreno et al [111] also described increments in VFA degradation due to the presence of soft carbon felt electrodes, evidencing the beneficial effect of conductive materials.…”
Section: Increasing Reactor Productivity By the Increase In Solid Content And Temperaturementioning
confidence: 94%
“…This increment was explained by the electron contribution from the microbial electrolysis system. Moreno et al [111] also described increments in VFA degradation due to the presence of soft carbon felt electrodes, evidencing the beneficial effect of conductive materials.…”
Section: Increasing Reactor Productivity By the Increase In Solid Content And Temperaturementioning
confidence: 94%
“…Nevertheless, this uncontrolled practice may have environmental problems, such as groundwater contamination due to infiltration, or greenhouse gas emissions [11]. Furthermore, lignocellulosic agroindustrial wastes and by-products lack of some macro and micronutrients [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Cheng and Zhong [23] have demonstrated that the use of swine manure as a co-substrate helps to neutralize the high VFAs concentration released by cotton stalk, emphasizing advantages related to the high buffer capacity provided by swine manure. Other authors have used a different strategy to minimize the acidification by VFAs in a biological process, by adding some micronutrients [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Fruit and vegetable wastes have high content of saccharides and disaccharides that are easily degradable by anaerobic microorganisms forming volatile fatty acids (VFAs) as intermediaries. When carbohydrates represent a large proportion of the feeding stream, a suppression of methanogenesis may be experienced with the overloading of the digester due to an initial VFA build-up leading to a decrease in reactor liqueur pH [ 48 ]. This VFA imbalance may negatively affect the production rate of biogas.…”
Section: The Effect Of Substrate Composition and Digestion Performmentioning
confidence: 99%